SISTEM PENDUKUNG KEPUTUSAN PENENTUAN URUTAN PRIORITAS PESERTA SERTIFIKASI GURU DI DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KABUPATEN BELU - Sinorio de Araujo, Domingos; Marisa, Fitri (DINAMIKA DOTCOM, 2015)
Today, many teachers in district have complained about certification process because the process is not transparent. Teacher young and working period less first got the chance to follow the certification process than teachers that in fact have longer work experience. Many people have blamed injustice caused by the factors collusion and nepotism are circulating among the Department of Education. This will not occur if the relevant authorities have been using an effective method to determining the priority list Participants as Decision Support Systems.The Decision Support System usingAnalitic HierarchyProses(AHP)method to make the priority list. AHP is one methods that can perform complex and detailed assessment criteria with a comprehensive framwork, consideration process then calculate weights for each criterion in determinis priorities certification testing in accordance with quotas.Â Keywords:certification,decision, hierarchy, priorities